2012
DOI: 10.1063/1.4731586
|View full text |Cite
|
Sign up to set email alerts
|

A morphology study on thermoelectric Al-substituted ZnO

Abstract: Al-substituted ZnO is a potential high temperature n-type thermoelectric material. The thermoelectric properties, the morphology and the microstructure of Zn 0.98 Al 0.02 O prepared by soft chemistry synthesis were studied and compared with samples synthesised by solid state reaction. The soft chemistry method produces samples with better connectivity of the grains and less structural defects leading to a lower electrical resistivity and a higher thermal conductivity than solid state reaction. The Seebeck coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Wu et al [127] have found that the presence of polyparaphenylene (PPP) nanoparticles in the Zn 0.95 Ni 0.05 O matrix was also effective in improving the ZT up to~0.54 at 1173 K. This improvement was achieved due to an increased power factor and a reduction in thermal conductivity. However, the values of k for these nanocomposites did not drop below 2 W/m·K even at 1000 K. For most other studies, the ZT did not exceed 0.15-0.3 [130,131].…”
Section: Nanostructuringmentioning
confidence: 92%
“…Wu et al [127] have found that the presence of polyparaphenylene (PPP) nanoparticles in the Zn 0.95 Ni 0.05 O matrix was also effective in improving the ZT up to~0.54 at 1173 K. This improvement was achieved due to an increased power factor and a reduction in thermal conductivity. However, the values of k for these nanocomposites did not drop below 2 W/m·K even at 1000 K. For most other studies, the ZT did not exceed 0.15-0.3 [130,131].…”
Section: Nanostructuringmentioning
confidence: 92%